The collective application of shorebird tracking data to conservation - Autumn‐Lynn Harrison; Candace Stenzel; Alexandra Anderson; Jessica Howell; Richard B. Lanctot; Marley Aikens; Joaquín Aldabe; Liam A. Berigan; Joël Bêty; Erik Blomberg; Juliana Bosi de Almeida; Andy J. Boyce; et al. (Conservation Biology, 2026)
Addressing urgent conservation issues, such as the drastic declines of North American migratory birds, requires creative, evidence‐based, efficient, and collaborative approaches. The abundance of over 50% of monitored North American shorebird populations has declined by over 50% since 1980. To address these declines, we developed a partnership of scientists and practitioners called the Shorebird Science and Conservation Collective (hereafter the collective ). The collective was founded to translate the combined findings of shorebird tracking data into on‐the‐ground conservation action. With advice from an advisory group, the collective acts as an intermediary whereby dedicated staff collate and analyze data contributions from scientists to support knowledge requests from conservation practitioners. In its first three years, data contributions from 75 organizations include over 7.1 million shorebird observations forming movement paths of 3420 individuals representing 36 species tracked across the Americas and have informed 18 conservation projects spanning education, land and species management, land conservation, and policy requests. Others engaged in translational science from big data could consider similar knowledge‐sharing models that prioritize usable data products, foster collaborative engagement between science experts and practitioners, build focused communities around topics or taxonomic groups, and employ a proof‐of‐concept phase to develop scalable solutions while making progress toward long‐term funding to sustain impact. As the volume of scientific data continues to grow, intermediaries, such as the collective, can be vital liaisons to rapidly integrate and interpret research to support conservation action. Dedicated to the memory of Shiloh Schulte and his conservation achievements for shorebirds.

Conservation aquaculture of wild-origin offspring preserves genetic diversity in an endangered population of white sturgeon - Peter Johnson; James Crossman; Andy Miller; Brent Nichols; Jason McLellan; Matthew Howell; Andrea Schreier (Conservation Genetics, 2025)
Conservation aquaculture programs that release fish to supplement wild populations can potentially capture greater genetic diversity by collecting offspring as embryos and larvae from wild spawning events than by producing them conventionally from broodstock. A conservation aquaculture program for the endangered white sturgeon population of the Upper Columbia River initially utilized wild broodstock for 14 years before fully transitioning to rearing wild-origin offspring in 2014. Here we evaluated the performance of this program in capturing the wild population’s genetic diversity since transitioning to wild-origin offspring. We analyzed genotypes of 325 tetrasomic single nucleotide polymorphism (SNP) markers in more than 5,000 offspring reared from 2014 to 2020 and over 1,000 wild adults from the population. Genetic diversity statistics were highly similar between each offspring year class and the wild adult population. We inferred sibship structure to estimate the total number of spawners (N s ) and effective number of breeders (N b ) represented within each year class and found values as high as 932.5 (95% CI 876–989) and 146.3 (95% CI 144–149), respectively, far surpassing the numbers included as broodstock. We further estimated N s and N b for three year classes with their individuals that died in aquaculture and found that on average, the mortality rate of 33.2% decreased N s by 21.5% and N b by 7.9%. Finally, we analyzed relationship coefficients to identify full-sibships spanning collection sites and found them in one year class, comprising 0.27% of all full-sibling pairs that year, demonstrating that the separate sites display negligible redundancy with respect to sibling families collected. Our results illustrate a robust performance by this program in representing the wild population’s diversity compared to broodstock approaches and support the adoption of utilizing wild-origin offspring in other conservation aquaculture programs when feasible.

An eight-founder wheat MAGIC population allows fine-mapping of flowering time loci and provides novel insights into the genetic control of flowering time - Laure Fourquet; Tobias Barber; Camila Campos-Mantello; Phil Howell; Beata Orman-Ligeza; Lawrence Percival-Alwyn; Gemma A. Rose; Hester Sheehan; Tally I. C. Wright; Friedrich Longin; Tobias Würschum; Dario Novoselovic; et al. (Theoretical and Applied Genetics, 2024)
Flowering time synchronizes reproductive development with favorable environmental conditions to optimize yield. Improved understanding of the genetic control of flowering will help optimize varietal adaptation to future agricultural systems under climate change. Here, we investigate the genetic basis of flowering time in winter wheat ( Triticum aestivum L.) using an eight-founder multi-parent advanced generation intercross (MAGIC) population. Flowering time data was collected from field trials across six growing seasons in the United Kingdom, followed by genetic analysis using a combination of linear modelling, simple interval mapping and composite interval mapping, using either single markers or founder haplotype probabilities. We detected 57 quantitative trait loci (QTL) across three growth stages linked to flowering time, of which 17 QTL were identified only when the major photoperiod response locus Ppd-D1 was included as a covariate. Of the 57 loci, ten were identified using all genetic mapping approaches and classified as ‘major’ QTL, including homoeologous loci on chromosomes 1B and 1D, and 4A and 4B. Additional Earliness per se flowering time QTL were identified, along with growth stage- and year-specific effects. Furthermore, six of the main-effect QTL were found to interact epistatically with Ppd-D1 . Finally, we exploited residual heterozygosity in the MAGIC recombinant inbred lines to Mendelize the Earliness per se QTL QFt.niab-5A.03 , which was confirmed to modulate flowering time by at least four days. This work provides detailed understanding of the genetic control of phenological variation within varieties relevant to the north-western European wheat genepool, aiding informed manipulation of flowering time in wheat breeding.

Properties of outer solar system pebbles during planetesimal formation from meteor observations - Peter Jenniskens; Paul R. Estrada; Stuart Pilorz; Peter S. Gural; Dave Samuels; Steve Rau; Timothy M.C. Abbott; Jim Albers; Scott Austin; Dan Avner; Jack W. Baggaley; Tim Beck; et al. (Icarus, 2024)

Lifetime of cm-sized zodiacal dust from the physical and dynamical evolution of meteoroid streams - Peter Jenniskens; Stuart Pilorz; Peter S. Gural; Dave Samuels; Steve Rau; Timothy M.C. Abbott; Jim Albers; Scott Austin; Dan Avner; Jack W. Baggaley; Tim Beck; Solvay Blomquist; et al. (Icarus, 2024)

Applying association mapping and genomic selection to the dissection of key traits in elite European wheat - Alison R. Bentley; Marco Scutari; Nicolas Gosman; Sebastien Faure; Felicity Bedford; Phil Howell; James Cockram; Gemma A. Rose; Tobias Barber; Jose Irigoyen; Richard Horsnell; Claire Pumfrey; et al. (Theoretical and Applied Genetics, 2014)

Genetic characterization and mapping of the Rht-1 homoeologs and flanking sequences in wheat - Edward P. Wilhelm; Rhian M. Howells; Nadia Al-Kaff; Jizeng Jia; Catherine Baker; Michelle A. Leverington-Waite; Simon Griffiths; Andy J. Greenland; Margaret I. Boulton; Wayne Powell (Theoretical and Applied Genetics, 2013)

Arsenic uptake and accumulation in rice (Oryza sativa L.) irrigated with contaminated water - Md. Joinal Abedin; J. Cotter-Howells; Andy A. Meharg (Plant and Soil, 2002)